The Legal Protection of House Ownership Credits - Bias Lintang Dialog; Gita Ayu Pramesti; Haris Budiman; Dikha Anugrah; Suwari Akhmaddhian (UNIFIKASI : Jurnal Ilmu Hukum, 2020)
The purpose of this study is to analyze the arrangement and the application of House Ownership Credits known as KPR based on the prevailing laws and regulations. This study employed a juridical-empirical approach. The juridical approach was used to analyze various laws and regulations. Meanwhile, the empirical approach was used to analyze the law which was viewed as a patterned community behavior in people’s lives that continually interacts and relates to social aspects. Reffering to the state regulation of public housing number 6 of 2011, the findings revealed the procurement of housing and settlements was supported by housing and financial aid in the form of housing subsidies through credits/home ownership financing. In addition, it is also required to submit a collateral in each application of a mortgage agreement with the bank. This collateral provides an assurance to the bank that the credit granted to the customers returns according to mutually agreed terms and minimizes the possible risk involved and arise in any credit disbursement. Meanwhile, in terms of providing credits to prospective debtors, the bank must have a confidence in the debtors’ ability or capability to repay the loan. In conclusion, credit is a loan-borrowing agreement between the bank and the other party that requires the borrower to pay off his debt with the amount of interest, compensation or profit sharing within a certain period of time. Besides, in the implementation of legal aspects for credit applicants, a general home ownership credit applicant is an individual or human who is not a legal entity. Humans who are not legally incorporated are legal subjects. Thus, a credit analyst and an authorized officer who work in a credit unit must be able to fully understand the ins and outs of the credit applicant’s legal aspects.Tujuan penelitian yaitu menganalisis Pengaturan dan Pelaksanaan Perjanjian Kredit Pemilikan Rumah (KPR) Berdasarkan Peraturan Perundang-Undangan. Metode Penelitian yang digunakan dalam penelitian ini adalah Pendekatan Yuridis Empiris. Pendekatan Yuridis digunakan untuk menganalisis berbagai peraturan perundang-undangan. Sedangkan pendekatan empiris digunakan untuk menganalisis hukum yang dilihat sebagai perilaku masyarakat yang berpola dalam kehidupan masyarakat yang selalu berinteraksi dan berhubungan dalam aspek kemasyarakat. Hasil penelitian yaitu peraturan menteri negara perumahan rakyat nomor 6 tahun 2011 tentang perumahan rakyat menyebutkan bahwa pengadaan perumahan dan pemukiman dengan dukungan bantuan pembiayaan perumahan dalam bentuk subsidi perumahan melalui kredit/pembiayaan pemilikan rumah. Setiap pelaksanaan perjanjian kredit pemilikan rumah pada bank, disyaratkan untuk menyerahkan jaminan. Fungsi jaminan ini adalah untuk memberikan keyakinan kepada bank bahwa kredit yang diberikan kepada nasabah dapat diterima kembali sesuai dengan syarat-syarat yang telah disepakati bersama, dan itu juga untuk meminimalisir resiko yang terkandung dan senantiasa dimungkinan dapat timbul dalam setiap pelepasan kredit.Berkaitan dengan pemberian kredit kepada calon debitur, maka pihak bank harus mempunyai keyakinan atas kemampuan atau kesanggupan pengembalian pinjaman kredit oleh debitur. Simpulan bahwa kredit adalah persetujuan atau kesepakatan pinjam-meminjam antara bank dan pihak lain yang mewajibkan peminjam untuk melunasi utangnya setelah jangka waktu tertentu dengan jumlah bunga, imbalan atau pembagian hasil keuntungan. Pelaksanaannya aspek hukum bagi pemohon-pemohon kredit. Pada umumnya pemohon kredit pemilikan rumah adalah perorangan atau manusia dan tidak berbadan hukum. Manusia yang tidak berbadan hukum adalah subyek hukum. Seorang analisis kredit dan pejabat yang bertugas di unit kerja perkreditan harus mampu memahami seluk beluk aspek-aspek hukum pemohon kredit